Study of the Adoption of IFRS 16, accounting, tax and financial involvement considering COVID-19 effect in Ecuador - Aguirre Naula, Fernanda (2021)
This paper performs an accounting analysis of the adoption of the International Financial Reporting Standard 16 (IFRS 16). Consider the implications of COVID-19, using a case study, from the perspective of the tenant. A descriptive and documentary research is applied, information on accounting guidelines, tax bases, theoretical framework and background were analyzed to evaluate the application of IFRS 16 and its effects on accounting records, financial metrics and taxes in a supposed empirical case. The results describe the impacts on the Lessee's Statement of Financial Position, Income Statement and Cash Flows; in addition to effects on its indicators such as indebtedness, solvency, profit before depreciation and amortization, taxes and interests (EBITDA) and earnings before taxes and interests (EBIT). The objective is to present accounting guidelines in the Adoption of IFRS 16 and promote discussion on its effects on financial information. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/1411